2002
DOI: 10.1002/14651858.cd000389
|View full text |Cite
|
Sign up to set email alerts
|

Mass media interventions: effects on health services utilisation

Abstract: BackgroundThe mass media frequently cover health related topics, are the leading source of information about important health issues, and are targeted by those who aim to influence the behaviour of health professionals and patients. ObjectivesTo assess the effects of mass media on the utilisation of health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
359
3
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(384 citation statements)
references
References 69 publications
14
359
3
8
Order By: Relevance
“…Concurrent supply availability and access to key services are crucial to persuade individuals motivated by media messages to act on them. Grilli and colleagues 22 concluded that mass media can have a positive eff ect on the use of health services and that more information is needed about whether mass media can increase use in populations with the greatest need. Evidence is moderate for the eff ect of mass media on immunisation coverage, HIV prevention, and use of oral rehydration therapy, but weaker for breastfeeding.…”
Section: Social Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent supply availability and access to key services are crucial to persuade individuals motivated by media messages to act on them. Grilli and colleagues 22 concluded that mass media can have a positive eff ect on the use of health services and that more information is needed about whether mass media can increase use in populations with the greatest need. Evidence is moderate for the eff ect of mass media on immunisation coverage, HIV prevention, and use of oral rehydration therapy, but weaker for breastfeeding.…”
Section: Social Marketingmentioning
confidence: 99%
“…Evidence is moderate for the eff ect of mass media on immunisation coverage, HIV prevention, and use of oral rehydration therapy, but weaker for breastfeeding. The three reviews [20][21][22] of social marketing emphasised the importance of an integrated package that includes mass media, training of health-care providers, and outreach to patients. Reviews that examined the eff ects of social marketing showed positive eff ects on promotion of awareness and use of insecticide-treated nets 23 and adop tion of recom mended practices for dengue pre vention.…”
Section: Social Marketingmentioning
confidence: 99%
“…Other methods to empower patients include satisfaction surveys, formal systems of accepting and responding to complaints, and publicly available health information [40]. The use of targeted mass media has also been demonstrated as effective in influencing utilization patterns [41].…”
Section: Resultsmentioning
confidence: 99%
“…The use of multimedia intervention has been proven to be effective and useful for childhood immunization programmes among sub-Saharan African countries and could be specially adopted for the HIV-exposed and infected children. 28 The use of interactive clinician-delivered communication tools has been found to improve mothers’ knowledge and understanding of good health. 29 …”
Section: Discussionmentioning
confidence: 99%